Acute exercise: response of HDL-C, LDL-C lipoproteins and HDL-C subfractions levels in selected sport disciplines - Sgouraki, E.; Tsopanakis, A.; Tsopanakis, C. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: High HDL levels has been shown to be associated with high endurance capacity. The acute effects of maximal endurance exercise (of short duration) (15 min) on low density lipoproteins-cholesterol (LDL-C), high density lipoproteins - cholesterol (HDL-C) and HDL subfractions HDL2 and HDL3 were examined, in order to determine whether the magnitude of response can be affected by maximal intensity of exercise (incremental stress test). METHODS: Male athletes (n=78) of national level, from four sport disciplines, volunteered to participate in this cross-sectional study; basketball (n=10), swimming (n=9), long distance (LD) running (n=23) and wrestling (n=35); also a group of non athletes as controls (n=19). Participants trained at least 2 hrs/day for more than 3 years; they were healthy, non-smokers and fasted 12 hrs before blood sampling. The ergometric test was a test for the estimation of maximal oxygen uptake on a treadmill ergometer based on a stepwise stress protocol. RESULTS: Immediately after a maximal effort all groups (controls included) showed significant HDL-C increases (p<0.001) from rest values, while LD running showed the highest values. HDL2 levels increased in LD running (p<0.001), basketball and wrestling, while HDL3 ones in all groups and controls (p<0.001). The HDL2 of all athletes showed the highest correlation (R=0.37**, p<0.01) with VO2max, even higher than HDL itself. CONCLUSIONS: Acute maximal endurance exercise (100&percent; VO2max) may induce acute modifications and intermolecular redistribution of HDL-C and subfractions. It is possible that the increased flux of lipids to HDL-C molecule may result from the regulatory action of lipoprotein lipase (LPL).